Inner chamber of the Belle II Central Drift Chamber - Chaiwongkhot K. (Institute of Electrical and Electronics Engineers Inc., 2015)
The Belle II Central Drift Chamber (CDC) is a cylindrical chamber filled with the helium based gas mixture inside. It consists of 56 layers (14,336 sense wires and 42,240 field wires). The group of innermost eight layers of axial wires called small-cell chamber is constructed for reducing the occupancy in the face of the large beam background. The small-cell chamber, including its conical aluminum endplates and the carbon fiber reinforced plastic (CFRP) inner cylinder, with radius 160 mm, has the minimum azimuthal cell size of 7 mm and has its wires strung independently before installation into the main chamber. The characteristic of the small-cell chamber, structure and wire configuration, for instance, are described. The results from the chamber test using the cosmic ray events are also presented. © 2013 IEEE.